« An Octopus / of ice » : stratigraphies d’un poème - Aurore Clavier (Transatlantica)
Fascinated by living and rock surfaces, and by their hidden depths, shaped by its multiple layers of discourse, “An Octopus,” the long poem Marianne Moore dedicated to the Mount Rainier glacier and national park at the beginning of the 1920s, invites to digging into deep time, as much as to the deciphering of modernity to which criticism has often reduced its interpretations. Nevertheless, unlike some of her contemporaries, the poet is spurred by no quest for a mythical foundation that could legitimize national history. Rather, the deep time that surfaces subverts ideal chronologies and allows for endless adaptations, hybridizations, and mutations, therefore redefining America far from too rigid notions of identity.